2020
DOI: 10.1002/jbt.22660
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate of pyrimidine derivative, the drug xymedon with succinic acid protects liver cells

Abstract: The aim of the study was to investigate the hepatoprotective properties of the conjugate of the xymedon drug substance with succinic acid (1a). The study presents an in vitro comparative evaluation of the cytotoxicity and cytoprotective properties of 1a and succinic acid on a cell line of normal human hepatocytes Chang Liver, and in vivo investigation of the ability of 1a to restore liver from the toxic damage caused by CCl4 in Wistar rats. It was shown that the cytotoxicity of 1a was 19.9 ± 0.8 mmol/L, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Histological Studies: Histological processingpreparation of paraffin sections, staining with Garris hematoxylin (BioVitrum, Russia), alcohol eosin (BioVitrum, Russia) were performed according to standard protocols described in more detail in our previous works [3][4][5][6][7] . Frozen sections were also prepared and stained with Sudan 4 (BioVitrum, Russia) according to standard protocols.…”
Section: Design Of the Experiments Involving The Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological Studies: Histological processingpreparation of paraffin sections, staining with Garris hematoxylin (BioVitrum, Russia), alcohol eosin (BioVitrum, Russia) were performed according to standard protocols described in more detail in our previous works [3][4][5][6][7] . Frozen sections were also prepared and stained with Sudan 4 (BioVitrum, Russia) according to standard protocols.…”
Section: Design Of the Experiments Involving The Experimental Animalsmentioning
confidence: 99%
“…Earlier data have shown that conjugation of Xymedon with some bioactive acids leads to an increase in the protective effect of the Xymedon molecule itself [3][4][5] . As a result of exploratory studies, Xymedon conjugate with L-ascorbic acid, among other studied conjugates, has a more pronounced and stable hepatoprotective effect.…”
mentioning
confidence: 99%
“…Succinic acid is able to activate the succinate receptor 1 (SUCNR1 or GPR91) in the liver and facilitate reparative processes in the liver [46]. Compared with the model group, the fermented edible grass group showed an increased level of intracellular succinic acid, indicating that fermented edible grass could reduce cell damage by providing succinic acid.…”
Section: Analysis Of Metabolic Pathwaymentioning
confidence: 99%
“…Гистологическую проводку, приготовление парафиновых срезов, окрашивание гематоксилином Гарриса (BioVitrum, Россия), спиртовым эозином (BioVitrum, Россия) осуществляли по стандартным протоколам, более подробно описанным в работах [4][5][6][7][8][9]. Приготовление замороженных срезов и окрашивание их суданом 4 (BioVitrum, Россия) также выполняли по стандартным протоколам.…”
Section: гистологические исследованияunclassified
“…Несвоевременно начатое лечение легких форм патологий печени, вызванных действием гепатотоксических веществ, может привести к более серьезным, вплоть до некротических повреждений [1]. Объектом настоящего исследования были лекарственный препарат на основе производного Ранее были получены данные, которые показали, что конъюгирование Ксимедона с некоторыми биологически активными кислотами приводит к усилению протекторного действия самой молекулы Ксимедона [3][4][5][6][7][8][9].…”
Section: Introductionunclassified